Pengaruh Penerapan Model Pembelajaran Kooperatif Tipe Make A Match Terhadap Hasil Belajar Matematika Kelipatan dan Faktor Bilangan Siswa Kelas IV SDN Borong - Rahmatillah; Ernawati , Ma’rup (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to determine the Effect of the Implementation of the Make A Match Type Cooperative Learning Model on the Learning Outcomes of Multiple Mathematics and Number Factors of Grade IV Students of SD Negeri Borong. The type of research used in this study is experimental research, especially Pre- experimental. The sample in this study was 25 students. Data collection techniques were carried out using learning outcome tests and observation sheets. Data analysis techniques in this study were descriptive data analysis techniques and inferential data analysis. The results of the study showed that the mathematics learning outcomes before the implementation of the Make A Match type cooperative learning model on the pretest with an average value of 65.2. While in the posttest increased with an average value of 86. The results of the t-test analysis on the effect of the Make A Match type cooperative learning model on student learning outcomes showed that the significance value obtained was good, namely the effect of the Make A Match type cooperative learning model on mathematics learning outcomes (Sig = 0.001) was smaller than the specified alpha value of 0.05 (0.001 <0.05). Based on the results obtained, it can be concluded that H0 is rejected and H1 is accepted, which states that there is an influence of the Make A Match type cooperative learning model on the mathematics learning outcomes of fourth grade students at Borong State Elementary School.